2022
DOI: 10.1155/2022/9735555
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin Ameliorates Renal Tubular Ferroptosis in Diabetes via SLC40A1 Stabilization

Abstract: Tubular injury has been shown to play a critical role in the morbidity of diabetic kidney disease (DKD); ferroptosis often occurs in tubules during renal disease development. This study was aimed at evaluating the inhibitory effects and potential mechanism of dapagliflozin (DAPA) against diabetic-related ferroptosis in the kidney. C57BL/6 mice were fed a high-fat diet (HFD) for 12 weeks, administered a small dose of streptozocin (STZ) for three consecutive days by intraperitoneal injection, and then orally adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 52 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Solute carrier family 40 member 1 (SLC40A1), also known as FPN1, is the only iron export protein discovered in mammals, and inhibition of it induces ferroptosis 63 . It has been demonstrated that dapagliflozin (DAPA) improves ferroptosis during diabetic renal tubular injury by stabilizing SLC40A1 64 . The NADPH oxidase CYBB (Nox2) is present in the cellular walls of all vascular walls, and NADPH oxidases (Nox) are the main sources of ROS in the vascular system 65 …”
Section: Discussionmentioning
confidence: 99%
“…Solute carrier family 40 member 1 (SLC40A1), also known as FPN1, is the only iron export protein discovered in mammals, and inhibition of it induces ferroptosis 63 . It has been demonstrated that dapagliflozin (DAPA) improves ferroptosis during diabetic renal tubular injury by stabilizing SLC40A1 64 . The NADPH oxidase CYBB (Nox2) is present in the cellular walls of all vascular walls, and NADPH oxidases (Nox) are the main sources of ROS in the vascular system 65 …”
Section: Discussionmentioning
confidence: 99%
“…In MDCK cells, NAC reduced high glucose-induced ferroptosis by increasing GPX4 expression [ 152 ]. Dapagliflozin, a glucose-lowering agent, has been shown to have cardiorenal protective effects, and recent studies have found that dapagliflozin also ameliorated ferroptosis in diabetic tubular injury by stabilizing SLC40A1 [ 153 ]. Empagliflozin also reduced renal tubular cell ferroptosis in DKD by enhancing the AMPK-mediated Nrf2 activation pathway [ 154 ].…”
Section: Ferroptosis and Ckdmentioning
confidence: 99%
“…Interestingly, SLC40A1, the only iron export protein discovered in mammals, displayed higher expression in the DAPA group compared to the HG group. The additional experiment proved that SLC40A1 ubiquitination was markedly elevated by HG administration in HK-2 cells but decreased by DAPA therapy, a drug that could directly combine and stabilize SLC40A1 through bioinformatics verification [ 51 ].…”
Section: Ferroptosis In Diabetic Nephropathymentioning
confidence: 99%